2020
DOI: 10.1016/j.esxm.2020.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Therapeutic Exercises for Men Affected by Premature Ejaculation: A Pilot Study

Abstract: Introduction Smartphone-delivered healthcare interventions allow patients to access services on demand when needed, improving motivation and compliance. However, the use of mobile health apps has been scarcely explored in sexual medicine. Aim To evaluate the effects of integrating psychological treatment for premature ejaculation (PE) with a mobile coaching app that offers therapeutic exercises on the patient’s smartphone. Methods This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Analysis of the data revealed significant pre‐post improvements in Premature Ejaculation Diagnostic Tool (PEDT) and Premature Ejaculation Profile (PEP) scores for the app group compared with those of the ‘treatment as usual’ group ( p <0.01). The frequency of patients with no‐PE condition for the app group after treatment was significantly higher than the frequency of patients with no‐PE condition for the ‘treatment as usual’ group ( p <0.001) 49 …”
Section: Narrative Summary and Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Analysis of the data revealed significant pre‐post improvements in Premature Ejaculation Diagnostic Tool (PEDT) and Premature Ejaculation Profile (PEP) scores for the app group compared with those of the ‘treatment as usual’ group ( p <0.01). The frequency of patients with no‐PE condition for the app group after treatment was significantly higher than the frequency of patients with no‐PE condition for the ‘treatment as usual’ group ( p <0.001) 49 …”
Section: Narrative Summary and Discussionmentioning
confidence: 71%
“…After removing 1736 papers through the title/abstract screening, 91 were retrieved as full text. Of the 91 full text, 36 studies were excluded because they were theoretical, opinion, focused on erectile dysfunction or included only pharmacological treatments, leaving 54 studies to be included in the systematic review 14–67 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data extracted from the included studies are summarized in Table 1 based on the type of intervention provided. Proportionately, 31.8% (n = 7) investigated different lifestyle, exercise and/or physical activities [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ]; 22.7% (n = 5) investigated herbal medicine supplements [ 65 , 66 , 67 , 68 , 69 ]; 18.2% (n = 4) investigated topical herbal applications [ 70 , 71 , 72 , 73 ]; 13.6% (n = 3) investigated acupuncture or electroacupuncture [ 74 , 75 , 76 ]; and 4.5% (n = 1) each investigated vitamin, mineral and/or nutraceutical supplements [ 77 ]; hyaluronic acid penile injection [ 78 ]; and music therapy [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 22 studies included, 95.5% (n = 21) studies investigated the effect of TCAM treatments on patients with PE [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 78 , 79 ], with only 1 study investigating RE [ 77 ]. No studies were identified that investigated TCAM for treating DE, anejaculation or other EjDs.…”
Section: Resultsmentioning
confidence: 99%